Absent left atrioventricular connection with right atrium connected to morphologically left ventricular chamber, rudimentary right ventricular chamber, and ventriculoarterial discordance. Problem of mitral versus tricuspid atresia. Issue 3 (September 1982) - Restivo, A; Ho, S Y; Anderson, R H; Cameron, H; Wilkinson, J L
Abstract : Four cases of absent left atrioventricular connection are reported. The observations from these cases have been used to emphasise problems concerning the use of the confusing terms "tricuspid" and "mitral" atresia to describe such hearts. One of the four cases represents a very uncommon condition since the rudimentary chamber was contralateral to the side of the absent emphasis given to the surgical implications of these anomalies.